Effects of quantum coherence in metalloprotein electron transfer. - Dorner, R; Goold, J; Heaney, L; Farrow, T; Vedral, V (2012)
Many intramolecular electron transfer (ET) reactions in biology are mediated by metal centers in proteins. This process is commonly described by a model of diffusive hopping according to the semiclassical theories of Marcus and Hopfield. However, recent studies have raised the possibility that nontrivial quantum mechanical effects play a functioning role in certain biomolecular processes. Here, we investigate the potential effects of quantum coherence in biological ET by extending the semiclassical model to allow for the possibility of quantum coherent phenomena using a quantum master equation based on the Holstein Hamiltonian. We test the model on the structurally defined chain of seven iron-sulfur clusters in nicotinamide adenine dinucleotide plus hydrogen:ubiquinone oxidoreductase (complex I), a crucial respiratory enzyme and one of the longest chains of metal centers in biology. Using experimental parameters where possible, we find that, in limited circumstances, a small quantum mechanical contribution can provide a marked increase in the ET rate above the semiclassical diffusive-hopping rate. Under typical biological conditions, our model reduces to well-known diffusive behavior.